The internet of things-based decision support system for information processing in intelligent manufacturing using data mining technology. (August 2020) - Guo, Yuan; Wang, Nan; Xu, Ze-Yin; Wu, Kai
Highlights: An intelligent decision support system (DSS) based on data mining technology is applied to enterprises. Data mining technology can analyze the statistical data from multiple angles and perspectives by modeling, classifying, and clustering a large amount of data. The system can make the decision-making of enterprises more effective and scientific and finally obtain the satisfactory decision-making results. Abstract: To comprehensively understand the decision information system for the information processing of the intelligent manufacturing under Internet of Things, an intelligent decision support system (DSS) based on data mining technology is applied to enterprises to establish an Internet of Things-based intelligent DSS for manufacturing industry, thereby supporting the decision-makers in making intelligent decisions through the intelligent DSS. The research results show that data mining technology can analyze the statistical data from multiple angles and perspectives by modeling, classifying, and clustering a large amount of data, as well as discovering the correlations between the data. Also, in statistical work, the data are counted, and their correlations are utilized to support the decision analysis. Therefore, it can be concluded that the establishment of intelligent DSS for enterprises in manufacturing industry and the utilization of data mining technology as the key technology to achieve the system can make the decision-making of the manufacturing enterprises more effective and scientific. Eventually, the satisfactory decision-making results can be obtained.